Resort & SPA Design - Siti Maryam Fauziah; Kemal Affandi; Arief Perdana Putra (Jurnal Arsitektur Archicentre, 2022)
The continuous growth of the times, particularly in West Bandung, necessitates that individuals continue to increase their potential and income in order to fulfill their basic demands. In this manner, community activities are expanding, but the community's physical and mental health are deteriorating due to the monotony and sameness of daily life, such as increased traffic congestion and deteriorating air quality. With the aforementioned conditions, facilities that can be used are required. Resort & Spa is one way to enhance the community's physical and mental health in the form of a place to vacation, rest, and relax in a new environment. This work employs a descriptive approach of analysis, namely the collection of data. This data is gathered via a literature review and comparative analysis of comparable initiatives, and is then examined. With a number of difficulties resulting from the fast growth of the times, one of which is an unhealthy atmosphere, the design of this Hotel & Spa seeks to create a pristine environment with the notion of returning to nature using the Eco Architecture theme. By integrating the principles and ideals of Eco Architecture to Resorts & Spas, it is anticipated that natural harm would be reduced. Spatial layout and circulation are planned with the environment's essentials, such as air conditioning, views, lighting, etc., in mind, with the aim of reducing energy use. In addition, the use of eco-friendly and indigenous materials, such as wood, reinforces the idea of this resort and spa, which is to return to nature.